INTENTION TO SEEK BREAST CANCER INFORMATION AMONG EMERGING ADULT IN FACEBOOK - Mohamed Samsudeen Sajahan; Nur Farhana Ngazawan; Arisya Nathasha Azrin (International Journal of Accounting, Finance and Business, 2022)
Rapid development of the Internet has gained tremendous attention as a way of disseminating health information, possibly resulting in diverse knowledge preferences, needs and health knowledge-seeking styles. Thus, the study is to investigate the influence of perceived autonomy, perceived relatedness, emotional support and informational support toward the intention to seek breast cancer information in Facebook among emerging adult in UiTM Merbok, Sungai Petani Kedah. The sampling technique used in this study is called purposive sampling. This study included a total of 90 female emerging adult students who were in their final year of diploma or degree studies and enrolled at UiTM Merbok. The finding indicates that there was positive relationship between perceived autonomy, perceived relatedness, emotional support, and informational support toward the intention to seek breast cancer information in Facebook among emerging adults.